Ideal Character of Muslim Generation of Industrial Revolution Era 4.0 and Society 5.0 - Dede Ramdani; Deasy Nurma Hidayat; Asep Sumarna; Icmiati Santika (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
This article was to find out the character Muslim prioritizes in facing the Industrial Revolution Era 4.0 and Society 5.0 The data analysis technique in this study uses categorical statistics from the distribution of questionnaires in the Bandung area and it’s surroundings. The results of the distribution of the questionnaire showed the ideal character sequence in Muslim children, namely honesty, discipline, responsibility, polite, confident, hardworking, tolerant, creative and innovative, caring, productive and religious. Then, it can be concluded that these characters can be the foundation of Muslim children facing the development of the industrial revolution era 4.0 and society 5.0. Keywords: Ideal Character, Muslim Generation, Industrial Revolution 4.0